[Mayor Billig and student at opening of MultiCultural Center], 1982 (1982)
San Luis Obispo Mayor Melanie Billig presents a document to a student at the podium during the Multicultural Center's dedication, held at the University Union plaza. Pictured behind them [left to right] include: Kevin and Mona Gridiron, David Sanchez, ASI president Dennis Hawk, President Baker, unidentified, unidentified, Quintard Taylor.